Cost Reducing Investment, Competition and Industry Dynamics - Emmanuel Petrakis; Santanu Roy (Tinbergen Institute, 1998)
We demonstrate the possibility of shake-out of firms and emergence of inter-firmheterogeneity along the (socially optimal) dynamic equilibrium path of a competitive industry with freeentry and exit, even when there is no uncertainty and all firms are ex ante identical with perfectforesight. Atomistic firms with upward sloping marginal cost curves undertake investment in firm-specific cost reduction. They earn negative net profit in early periods, compensated later by strictlypositive net profits; no entry occurs after the initial time period. Some firms may exit before others evenwhile other firms earn positive net profit.
Keywords: D41; D92; L11; O31; 330; Cost Reducing Investment; Industry Dynamics; Learning; Competitive Equilibrium; Shake Out; Investitionsentscheidung; Rationalisierung; Wettbewerb; Industrie; Theorie